2019
DOI: 10.1016/j.bja.2019.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal lentivirus-mediated RNA interference targeting nerve growth factor attenuates myocardial ischaemia–reperfusion injury in rat

Abstract: Background: Nerve growth factor (NGF) has been implicated in hyperalgesia by sensitising nociceptors. A role for NGF in modulating myocardial injury through ischaemic nociceptive signalling is plausible. We examined whether inhibition of spinal NGF attenuates myocardial ischaemiaereperfusion injury and explored the underlying mechanisms. Methods: In adult rats, lentivirus-mediated short-hairpin RNA targeted at reducing NGF gene expression (NGF-shRNA) or a transient receptor potential vanilloid 1 (TRPV1) antago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Studies have confirmed that the cardiomyocyte H/R model can be used as an effective method to simulate myocardial I/RI in the cardiomyocyte culture model [ 17 ]. And the duration of hypoxia is a crucial factor for the success of the H/R model.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that the cardiomyocyte H/R model can be used as an effective method to simulate myocardial I/RI in the cardiomyocyte culture model [ 17 ]. And the duration of hypoxia is a crucial factor for the success of the H/R model.…”
Section: Discussionmentioning
confidence: 99%
“…TRPV1 also affects circulation through the spinal cord neurons and DRG neurons. The experiment shows that on the myocardial ischemia-reperfusion, additional activation of the spinal cord TRPV1 contributed to a severer myocardial injury; however, intrathecal administration of the TRPV1 antagonist capsazepine reduced the size of the infarct area [ 23 ].…”
Section: Keyword Co-occurrencementioning
confidence: 99%
“…Nerve growth factor (NGF) has a key role in upregulating TRPV1 expression in peptidergic sensory neurons of adult rats [ 83 ] via the NGF-TrkA signaling. Knocking down spinal NGF had myocardial protective effect against ischemic injury similarly to the effect of capsazepine in a rat AMI model [ 84 , 85 ]. However, it is important to note that the sample size used in these studies were low, n = 3 and n = 6, respectively.…”
Section: The Capsaicin-sensitive Sensory Nerves and The Trpv1 Recementioning
confidence: 99%